ASSESSEMENT OF THE Preservative Effect of Zingiber Officinale and Syzygium aromaticum on the shelf life of Kunun aya - Mohammed, Hanifa (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Spices and herbs have been reported to be potent source of natural antioxidants. Spices are known to impact flavor and improve overall organoleptic quality of foods. The use of naturally occurring materials like spices as preservatives has been proved to be a promising alternative to the use of chemicals. The effect of ginger and clove extract on the storability of kunun aya were investigated in this study. Fresh ginger and clove were collected, identified, air dried and extracted using distilled water. Kunun aya was prepared in the laboratory with the addition of the spices extracts at different concentrations. The samples were stored at room temperature and the effects of spices extracts on their proximate, physiochemical parameters, microbial and sensory properties were evaluated. The result of proximate analyses revealed the moisture content of the kununaya to be between 83.98-80.54 in ginger spiced kunun aya and 81.67 to 78.15 in clove spiced kunun aya, the crude protein ranges from 3.96 to 4.52 in ginger spiced kunun aya and 3.07-3.93 in clove spiced kunun aya. The ash content ranges from 0.28-0.23 and 0.25to 0.23 in both the ginger and clove respectively. The fat content ranges from 3.78-2.44 in clove and 3.54-2.31 in ginger spiced kunun aya and finally the carbohydrate content ranges from8.24-12.35 in ginger and 11.24-14.87 in clove spiced kunun aya. Slight increase in temperature was recorded in all the samples but there was a marginal decrease in pH as storage time increases. The bacterial count of kunun aya treated with ginger extract ranged from 1.4 x 105_ 3.1 x 106 CFU/ml, the total fungal count ranged from 1.0 x 105 - 9.7 x105 CFU/ml. bacterial count of kunun aya treated with clove extract ranged from 1.8 x 105_3.5 x 106 CFU/ml while the total fungal count ranged from 8.0 x 104_8.6 x 105 CFU/ml. There was a significant difference between the sensory attributes of the treated kunun aya and the control samples with the control sample having the highest score rating.